The constellation of dietary factors in adolescent acne: a semantic connectivity map approach. (2nd December 2014) - Grossi, E.; Cazzaniga, S.; Crotti, S.; Naldi, L.; Di Landro, A.; Ingordo, V.; Cusano, F.; Atzori, L.; Tripodi Cutrì, F.; Musumeci, M.L.; Pezzarossa, E.; Bettoli, V.; et al.
Abstract: Background: Different lifestyle and dietetic factors have been linked with the onset and severity of acne. Objective: To assess the complex interconnection between dietetic variables and acne. Methods: This was a reanalysis of data from a case–control study by using a semantic connectivity map approach. 563 subjects, aged 10–24 years, involved in a case–control study of acne between March 2009 and February 2010, were considered in this study. The analysis evaluated the link between a moderate to severe acne and anthropometric variables, family history and dietetic factors. Analyses were conducted by relying on an artificial adaptive system, the Auto Semantic Connectivity Map (AutoCM). Results: The AutoCM map showed that moderate‐severe acne was closely associated with family history of acne in first degree relatives, obesity (BMI≥30), and high consumption of milk, in particular skim milk, cheese/yogurt, sweets/cakes, chocolate, and a low consumption of fish, and limited intake of fruits/vegetables. Conclusion: Our analyses confirm the link between several dietetic items and acne. When providing care, dermatologists should also be aware of the complex interconnection between dietetic factors and acne.